2022
DOI: 10.1039/d2sc02282f
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven molecular motors embedded in covalent organic frameworks

Abstract: The incorporation of molecular machines into the backbone of porous framework structures will facilitate nano actuation, enhanced molecular transport, and other out-of-equilibrium host-guest phenomena in well-defined 3D solid materials. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 92 publications
(130 reference statements)
0
21
0
1
Order By: Relevance
“…In contrast to the increased cell parameter a, the slight reduction in pore diameter might be affected by increasing stacking disorder, e.g. random offset-stacking of the layers 18,21,22 upon oxidation to the nitrone, likely introduced by the reorganization of the local structure of the linkages affecting interlayer interactions. 23,24 Despite these changes in the structure, the material shows porosity after the conversion of the linkage, evident from a BET surface area of 664 m 2 g -1 for NO-PI-3-COF (Figure S20).…”
Section: Materials Synthesis and Analysismentioning
confidence: 99%
“…In contrast to the increased cell parameter a, the slight reduction in pore diameter might be affected by increasing stacking disorder, e.g. random offset-stacking of the layers 18,21,22 upon oxidation to the nitrone, likely introduced by the reorganization of the local structure of the linkages affecting interlayer interactions. 23,24 Despite these changes in the structure, the material shows porosity after the conversion of the linkage, evident from a BET surface area of 664 m 2 g -1 for NO-PI-3-COF (Figure S20).…”
Section: Materials Synthesis and Analysismentioning
confidence: 99%
“…However, recent studies that examine both Bragg and diffuse scattering have suggested signicant local structural deviations from the average structure in these supramolecular materials. [39][40][41] In one example, Terban and coworkers demonstrated that modeling of interlayer stacking disorder not captured in the average structure was necessary to account for the pair distribution functions. 41 While deviations in the interlayer stacking of 2D COFs may be expected given the relatively weak dispersive forces responsible for the ordering of layers, the extent of disorder in 3D crystalline COFs is not well studied.…”
Section: Pair Distribution Function Analysismentioning
confidence: 99%
“…Consequently, the structure-property relationship of these compounds remains virtually unknown, which poses a signicant challenge for the design of overcrowded olenbased bistable chiroptical switches for selected functions and as such constitutes a major limitation to their applications and future development. 50 Here we present a systematic study on the functionalization of the uorene-derived "bottom part" of overcrowded alkenebased bistable chiroptical photoswitches (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the structure–property relationship of these compounds remains virtually unknown, which poses a significant challenge for the design of overcrowded olefin-based bistable chiroptical switches for selected functions and as such constitutes a major limitation to their applications and future development. 50 …”
Section: Introductionmentioning
confidence: 99%